2011
DOI: 10.1177/0892705711406161
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Single and Hybrid Aluminum and Silver Fillers Filled High-Density Polyethylene Composites

Abstract: The electrical and thermal properties of two series of composites, single-filler aluminum (Al) and silver (Ag) and hybrid-filler Al/Ag-filled high-density polyethylene (HDPE) composites, are reported. The composites were prepared by mixing using an internal mixer followed by compression molding. Studies on the electrical properties of single-filler composites showed an insulator-to-conductor transition in HDPE/Ag and HDPE/Al between 45-55 wt% and 55-65 wt% filler loadings, respectively. This is due to the form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Natural fibers have lighter weight and better qualities for aviation and automobiles. 24 On the other hand, green fibers encounter a number of problems in terms of attaining better-quality mechanical properties, water absorption, fiber variation, flammability, toughness, and further changes depending upon environmental circumstances. Previous research studies have shown that glass fibers are hydrophobic in nature and they are humidity resistant.…”
Section: Natural Fiber Composite Challengesmentioning
confidence: 99%
“…Natural fibers have lighter weight and better qualities for aviation and automobiles. 24 On the other hand, green fibers encounter a number of problems in terms of attaining better-quality mechanical properties, water absorption, fiber variation, flammability, toughness, and further changes depending upon environmental circumstances. Previous research studies have shown that glass fibers are hydrophobic in nature and they are humidity resistant.…”
Section: Natural Fiber Composite Challengesmentioning
confidence: 99%
“…[1][2][3] Among the nanocomposites, especially, metal-based materials, such as, silver (Ag)-polymer nanocomposites, are of special interest. [4][5][6] This is because nanoscale metal particles such as Ag and gold provide a very exciting research field due to their interesting optical, electronic, magnetic, and catalytic properties.…”
Section: Introductionmentioning
confidence: 99%
“…Research activities on inorganic-polymer nanocomposites are witnessed an exponential growth due to many new characters, such as thermal, electrical, mechanical, optical properties, and so on, which can be widely used in optical materials, electricity materials, biomedical materials, information materials, and other fields. [1][2][3] Among the nanocomposites, especially, metal-based materials, such as, silver (Ag)polymer nanocomposites, are of special interest. [4][5][6] This is because nanoscale metal particles such as Ag and gold provide a very exciting research field due to their interesting optical, electronic, magnetic, and catalytic properties.…”
Section: Introductionmentioning
confidence: 99%
“…The development of modern industry enabled the range of the plastic modification spread from inorganic particles to metallic particles and nanoparticles. 1 3 These particles, particularly metallic particles, made the preparation technology become complex and difficult due to the compatibility of metal powders and polymers. 4 Meanwhile, the performance of polymer/metal composites was affected by the shape, content, size, dispersion, and category of metallic particles.…”
Section: Introductionmentioning
confidence: 99%